Effect of groundnut cake supplementation during the dry season on productivity characteristics of N'Dama cows under village husbandry conditions in The Gambia - Little, D.A.; Riley, J.A.; Agyemang, K.; Jeannin, P.; Grieve, A.S.; Badjie, B.; Dwinger, R.H. (1991)
Reports an experiment in which small quantities of groundnut cake were fed during the dry season to lactating N'Dama cows maintained under village husbandry conditions in The Gambia, resulting in significant increases in quantities of milk offtake and in rates of growth of the suckling calves, and in significant losses of maternal liveweight during these feeding periods; and presents the results of a preliminary cost-benefit analysis as a promising basis for improvement of village husbandry systems in the Sudano-Sahelian zone of sub-Saharan Africa.